Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.7326/0003-4819-160-1-201401070-00731
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Risk for Invasive Meningococcal Disease Among Persons With HIV

Abstract: New York City Tax Levy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 22 publications
4
46
1
4
Order By: Relevance
“…In studies from South Africa, the United States, and the United Kingdom, the incidence of meningococcal disease in HIV-infected persons ranged from 3.4 to 6.6 per 100,000 (relative risk = 5-13 compared with HIV-uninfected persons) ( Table 1) (6-9). Among HIV-infected persons, a low CD4 count or high viral load were associated with an increased risk (7). Similar increased risk for meningococcal disease was observed for both males and females with HIV infection (7,9).…”
Section: Meningococcal Disease In Hiv-infected Personssupporting
confidence: 53%
See 2 more Smart Citations
“…In studies from South Africa, the United States, and the United Kingdom, the incidence of meningococcal disease in HIV-infected persons ranged from 3.4 to 6.6 per 100,000 (relative risk = 5-13 compared with HIV-uninfected persons) ( Table 1) (6-9). Among HIV-infected persons, a low CD4 count or high viral load were associated with an increased risk (7). Similar increased risk for meningococcal disease was observed for both males and females with HIV infection (7,9).…”
Section: Meningococcal Disease In Hiv-infected Personssupporting
confidence: 53%
“…Among HIV-infected persons, a low CD4 count or high viral load were associated with an increased risk (7). Similar increased risk for meningococcal disease was observed for both males and females with HIV infection (7,9).…”
Section: Meningococcal Disease In Hiv-infected Personssupporting
confidence: 53%
See 1 more Smart Citation
“…However, results of surveillance data analysis from 2003 to 2007 in patients of all ages conducted in South Africa showed that HIV was associated with a higher incidence of MD and higher case fatality ratios. 30 Other recent studies, including two from the United States from the 2000s, have found a 13-fold and 10-fold greater risk of MD for those with HIV, 65 although the findings on case fatality ratios were less clear. Importantly, patients in these recent studies were receiving antiretroviral therapy and a good standard of healthcare.…”
Section: Meningococcal Vaccination and Hivmentioning
confidence: 89%
“…A single retrospective study suggests a higher risk in HIV-infected patients living in New York City, with a 10-fold increased risk (95% CI, 7.2 to 14.1); particularly in patients with less than 200 CD4/mm 3 ; data on smoking status and co-morbidities are missing. 71 Outbreaks of invasive meningococcal C infections among MSM, with or without HIV infection, described in the US and Europe, have prompted vaccination campaigns targeting MSM. 72,73 A casecontrol study, conducted in the context of a prolonged outbreak of serogroup C meningococcal disease among MSM in New York City, identified 2 key risk factors: having a sexually transmitted disease during the year before diagnosis and having used methamphetamine or cocaine during the month before illness onset.…”
Section: Meningococcal Vaccinementioning
confidence: 99%